The breakthrough : politics and race in the age of Obama - Ifill, Gwen (New York : Doubleday, 2009)
Veteran journalist Ifill sheds new light on the impact of Barack Obama's presidential victory and introduces the emerging African American politicians forging a new path to political power. Ifill argues that the Black political structure formed during the Civil Rights movement is giving way to a generation who are the direct beneficiaries of the struggles of the 1960s. She offers detailed profiles of such prominent leaders as Newark Mayor Cory Booker, Massachusetts Governor Deval Patrick, and U.S. Congressman Artur Davis of Alabama, as well as numerous up-and-coming figures. Drawing on exclusive interviews with power brokers such as President Obama, Colin Powell, Vernon Jordan, the Reverend Jesse Jackson, his son Congressman Jesse Jackson Jr., and many others, as well as her own observations and analysis of such issues as generational conflict, the race/gender clash, and the "black enough" conundrum, Ifill shows why this is a pivotal moment in history.--From publisher description.
Breaking through -- The generational divide -- Barack Obama -- The race/gender clash -- Artur Davis -- Legacy politics -- Cory Booker -- The politics of identity -- Deval Patrick -- The next wave.
Includes bibliographical references (p. [247]-264) and index.
Keywords: Obama, Barack -- Influence; African American politicians -- History; African Americans -- Politics and government; Presidents -- United States -- Election -- 2008.; United States -- Race relations; United States -- Politics and government